Um caso de aplicação da lógica fuzzy : o modelo Coppe-Cosenza de hierarquia fuzzy - Toledo, Olga Moraes. (UFRJ, 2004)
[PT]O objetivo central do presente estudo é a pesquisa do Modelo Coppe-Cosenza de Hierarquia "Fuzzy" a partir de sua concepção como Modelo específico para Localização Industrial e sua generalização como Modelo de Apoio à Decisão fundamentado em Lógica "Fuzzy". Esta análise se evidencia através do estudo do Modelo, dos conceitos básicos sobre os quais ele se baseia, e também através das suas aplicações mais relevantes, que suscitaram o interesse efetivo e se tornaram-se referência para a sua efetiva aplicação e validação.[EN]The applications of Fuzzy Logic have been spread in different directions. The interpretation of data through Fuzzy Logic is a very natural way, and intuitively plausible, for the elaboration and solution of problems. This work presents a conceptual view of the Coppe-Cosenza Fuzzy Hierarchy Model. The focus is the research on the Coppe-Cosenza Fuzzy Hierarchy Model from its conception as an specific model for Industrial Localization and its generalization as a Decision Support Model, grounded in Fuzzy Logic: This analysis is shown clearly through the effective study of a Model, of the basic concepts on which its is grounded, and also through its most relevant applications, wich have provoked this particular interest and have became a reference for its applications and its validation.